Unraveling Intricacies of Monsoon Attributes in Homogenous Monsoon Regions of India - Saini, Atul; Sahu, Netrananda; Duan, Weili; Kumar, Manish; Avtar, Ram; Mishra, Manoranjan; Kumar, Pankaj; Pandey, Rajiv; Behera, Swadhin (Frontiers in Earth Science, 2022)
India observes the summer monsoon in JJAS season and the livelihood security of a huge population depends on it. The impact of the monsoon onset timing, length of monsoon season, rainfall amount and related extreme events is huge on the Indian economy. Therefore, understanding the inherent intricacies needed a detailed investigation. In five homogenous monsoon regions of India, the trend of monsoon onset and length of monsoon season is examined. The association between (i) monsoon onset ~ rainfall amount, (ii) length of monsoon season ~ rainfall amount and (iii) monsoon onset ~ length of monsoon season is investigated. Subsequently, the behaviour of rainfall and extreme excess days in ±1 standard deviation (SD) length of monsoon season is also examined in detail. The trend for monsoon onset shows late-onset in all the homogenous monsoon regions except the Northeast region. Length of monsoon season is found increasing significantly with high magnitude in West Central and Northwest regions. A significantly strong negative correlation (~ -0.6) for monsoon onset timing ~ length of monsoon season is observed. Therefore, the change in rainfall anomaly, extreme excess days, and rainy days is done concerning the length of the monsoon season. In cases of -1 SD (+1 SD) length of monsoon season; rainfall anomaly and extreme excess days are low (high) in most parts of the homogenous monsoon regions. Extreme excess days showed a significant association with rainy days, which indicates a high possibility of rainy days converting into extreme excess days. However, the increase in extreme excess days in +1 SD length of monsoon season is limited to a great extent in JJAS and June only. Morlet wavelet power spectrum shows the delay (advance) of power in -1SD (+1 SD) length of monsoon season.